2017
DOI: 10.3389/fpls.2017.00662
|View full text |Cite
|
Sign up to set email alerts
|

Embolized Stems Recover Overnight in Zea mays: The Role of Soil Water, Root Pressure, and Nighttime Transpiration

Abstract: It is not currently well-understood how much xylem conductance is lost in maize plants during the day, if conductance is recovered during the night, or what soil water conditions are required for recovery to take place. To answer these questions we designed a greenhouse experiment whereby two genetically dissimilar maize genotypes were subjected to a level of water stress commonly experienced in the field (Ψxylem ∼-2 MPa). We then measured the loss of stem-specific conductivity associated with this level of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 51 publications
6
46
1
Order By: Relevance
“…Root pressure has been considered as a potential mechanism involved in both repair of embolized vessels and water supply to shoots in the absence of transpiration (Cao, Yang, Zhang, & Brodribb, 2012;Charrier et al, 2016;Ewers, Cochard, & Tyree, 1997;Knipfer, Eustis, Brodersen, Walker, & McElrone, 2015;Steudle, 2001). However, whereas root pressure has been reported to occur in a variety of crop species such as barley (Knipfer & Fricke, 2010), maize (Gleason et al, 2017), rice (Stiller et al, 2003), sugarcane (Meinzer, Grantz, & Smit, 1991) and tomato (De Swaef, Hanssens, Cornelis, & Steppe, 2013), xylem repair in herbaceous and woody species has been seldom observed (Choat et al, 2019;Lens et al, 2016;Sperry, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Root pressure has been considered as a potential mechanism involved in both repair of embolized vessels and water supply to shoots in the absence of transpiration (Cao, Yang, Zhang, & Brodribb, 2012;Charrier et al, 2016;Ewers, Cochard, & Tyree, 1997;Knipfer, Eustis, Brodersen, Walker, & McElrone, 2015;Steudle, 2001). However, whereas root pressure has been reported to occur in a variety of crop species such as barley (Knipfer & Fricke, 2010), maize (Gleason et al, 2017), rice (Stiller et al, 2003), sugarcane (Meinzer, Grantz, & Smit, 1991) and tomato (De Swaef, Hanssens, Cornelis, & Steppe, 2013), xylem repair in herbaceous and woody species has been seldom observed (Choat et al, 2019;Lens et al, 2016;Sperry, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that root pressure induces refilling in the field, possibly only under high soil moisture conditions, or that refilling may have occurred in this study if plants were monitored for a longer period of time after rewatering. Some research has suggested that daily losses of xylem conductance are repaired overnight in rice leaves (Stiller & Lafitte, ), while others have visualized refilling in the stems of maize (Gleason et al, ). It should be noted that these studies used methods that involved excised plant material, unlike the non‐invasive in vivo method that was used in this study as it minimizes the risk of exogenous embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Grasses represent a significant technical challenge for measuring cavitation due to their small size, fragility, and vascular arrangement (Bramley et al, ; Cochard et al, ; Jansen, Schuldt, & Choat, ). In addition, it is generally assumed that cavitation in grasses may not be as catastrophic as it is in woody plants due to the presence of sufficient root pressure to repair embolism in grasses such as wheat and bamboo (Cao, Yang, Zhang, & Brodribb, ; Gleason et al, ; Ryu, Hwang, & Lee, ; Trillo & Fernandez, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we recognize that species may diverge from this optimal solution if fitness in a particular environment places a premium on other traits, such as height or mechanical safety, in general we might expect limited leaf size and plant size when the hydraulic radii or conduit number is constrained at the base of the plant. However, we do note that the occurrence of emboli (from freezing–thawing or low water potential) do not necessarily represent insurmountable impediments to water transport in either gymnosperm or angiosperm species (McCulloh et al ., ; Secchi & Zwieniecki, ; Trifilò et al ., ; McCulloh & Meinzer, ; Gleason et al ., ).…”
Section: Discussionmentioning
confidence: 99%